Sustainable tourism : contribution to economic growth and sustainable development (UN New YorkUS, 2013)
Seeks to identify the key issues that should be addressed in considering the contributions of tourism to sustainable development. Reviews the relative importance of the tourism sector from the global and national perspective. Assesses the potential direct and indirect impacts of tourism on local economies and its potential role in poverty reduction and inclusive growth. Addresses the challenges posed by the sector, specifically damage to the environment and cultural heritage. Examines how the sector could be made more sustainable and how its contribution to sustainable development could be enhanced.
Keywords: TOURISM